Homeward bound: a centenary of home mechanical ventilation - Hind,M; Polkey,MI; Simonds,AK (American Journal of Respiratory and Critical Care Medicine, 2017)
The evolution of home mechanical ventilation is an intertwined chronicle of negative and positive pressure modes and their role in managing ventilatory failure in neuromuscular diseases and other chronic disorders. The uptake of noninvasive positive pressure ventilation has resulted in widespread growth in home ventilation internationally and fewer patients being ventilated invasively. As with many applications of domiciliary medical technology, home ventilatory support has either led or run in parallel with acute hospital applications and has been influenced by medical and societal shifts in the approach to chronic care, the creation of community support teams, a preference of recipients to be treated at home, and economic imperatives. This review summarizes the trends and growing evidence base for ventilatory support outside the hospital.